2017
DOI: 10.1002/brb3.732
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal resting state effective connectivity within the default mode network in major depressive disorder: A spectral dynamic causal modeling study

Abstract: IntroductionUnderstanding the neural basis underlying major depressive disorder (MDD) is essential for the diagnosis and treatment of this mental disorder. Aberrant activation and functional connectivity of the default mode network (DMN) have been consistently found in patients with MDD. It is not known whether effective connectivity within the DMN is altered in MDD.ObjectsThe primary object of this study is to investigate the effective connectivity within the DMN during resting state in MDD patients before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…the DMN was also reduced in FEDN, consistent with a recent rs-fMRI study that reported reduced EC from the left parietal cortex to other DMN regions in MDD patients who were antidepressant drug-free for at least 3 months (Li et al, 2017). In addition, we observed the EC between the cerebellum and other DMN regions substantially decreased in FEDN, in line with previous studies (Guo et al, 2013;Liu et al, 2012) …”
Section: Altered Ec Within the Dmnsupporting
confidence: 92%
See 2 more Smart Citations
“…the DMN was also reduced in FEDN, consistent with a recent rs-fMRI study that reported reduced EC from the left parietal cortex to other DMN regions in MDD patients who were antidepressant drug-free for at least 3 months (Li et al, 2017). In addition, we observed the EC between the cerebellum and other DMN regions substantially decreased in FEDN, in line with previous studies (Guo et al, 2013;Liu et al, 2012) …”
Section: Altered Ec Within the Dmnsupporting
confidence: 92%
“…The majority of DCM studies on MDD have used task-based fMRI yet there are still a handful of reports with rs-fMRI (Hyett, Breakspear, Friston, Guo, & Parker, 2015;Kandilarova, Stoyanov, Kostianev, & Specht, 2018;Li et al, 2017). Hyett et al (2015) used stochastic DCM to infer spontaneous interactions among five canonical resting-state networks (DMN, EXE, bilateral anterior insula, and left and right frontoparietal attention networks) from 16 participants with melancholia, 16 with nonmelancholic depression, and 16 healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCC is considered one of the hubs of the DMN with a general role in attention modulation, and in episodic and working memory. Declined influences from left LP to PCC in MDD compared with HC group have been reported in a recent study (Li et al, 2017b ). This dysfunction of the connection may be related to the impaired signals propagate from one region to another in DMN.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, the majority of the effective connectivity studies in depressed patients have focused on task-related fMRI probing cognitive and emotional processing ( 21 23 ) with only a few reports on resting state fMRI ( 24 , 25 ). By means of spectral DCM, Li et al ( 24 ) investigated the DMN in a sample of healthy controls and depressed patients before and after treatment.…”
Section: Introductionmentioning
confidence: 99%